2020
DOI: 10.1101/2020.09.10.20192195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mathematical Modeling and a Month Ahead Forecast of the Coronavirus Disease 2019 (COVID-19) Pandemic: An Indian Scenario

Abstract: India, the second-most populous country in the world, has been lately witnessing a daily surge in the COVID-19 infected cases. India is currently among the worst-hit nations worldwide, due to the COVID-19 pandemic, and ranks just behind Brazil and USA. In order to prevent the further worsening of the situation, predicting the future course of the pandemic is of utmost importance. In this paper, we model the past trajectory (March 01, 2020 - July 25, 2020) and make a month-long (July 26, 2020 - August 24, 2020)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The r3, r4, and r5 generated within an interval of [0,1] and are random number. F represents a flag that exchanged the direction of the search, and identified by (10):…”
Section: Honey Badger Algorithm (Hba)mentioning
confidence: 99%
“…The r3, r4, and r5 generated within an interval of [0,1] and are random number. F represents a flag that exchanged the direction of the search, and identified by (10):…”
Section: Honey Badger Algorithm (Hba)mentioning
confidence: 99%
“…Air pollution can be referred to as the release of pollutants into the air that may be injurious to the people’s health as well as the environment. Some ground-based studies found that national lockdown by the COVID-19 outbreak condition has slowed down the air pollution process all over the world (Halder et al 2021 ; Ganiny and Nisar 2021 ). The first report of COVID-19 outbreak recorded in Wuhan, China and affirmed as anthroponoses causing difficulty breathing, aches and pains and SARS (WHO 2020 ).…”
Section: Introductionmentioning
confidence: 99%